2012
DOI: 10.2223/jped.2231
|View full text |Cite
|
Sign up to set email alerts
|

Use of off-label and unlicensed drugs in the neonatal intensive care unit and its association with severity scores

Abstract: Objective: To analyze the frequency of unlicensed (UL) and offlabel (OL) prescriptions in neonates admitted to the neonatal intensive care unit of a tertiary care hospital and to determine their association with patients' severity. Methods:Observational cohort study including drugs prescribed during hospitalization of neonates over a 6-week period between July and August 2011. The drugs were classified as UL and OL for dose, frequency, presentation, age group, or indication, according to an electronic list of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
3
10

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 20 publications
(24 reference statements)
3
32
3
10
Order By: Relevance
“…12,13,19 With regard to the higher number of drugs necessary in preterm neonates (median = 4), it confirms the current knowledge that younger, lighter and most vulnerable newborns receive more drugs than the more matures. [13][14][15] Beyond the classical division into off-label and unlicensed drugs, we chose to add 'undetermined state approval' and 'contraindicated' categories, in order to be more precise in data analysis. However, typically they are included in off-label category by other authors.…”
Section: Discussion Prescription In Neonatal Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13,19 With regard to the higher number of drugs necessary in preterm neonates (median = 4), it confirms the current knowledge that younger, lighter and most vulnerable newborns receive more drugs than the more matures. [13][14][15] Beyond the classical division into off-label and unlicensed drugs, we chose to add 'undetermined state approval' and 'contraindicated' categories, in order to be more precise in data analysis. However, typically they are included in off-label category by other authors.…”
Section: Discussion Prescription In Neonatal Settingmentioning
confidence: 99%
“…9,12 For this reason, just like sick full-term newborns are more exposed to the off-label/unlicensed medications, the most premature and low birth weight neonates receive the greatest number of drugs. [13][14][15] Moreover, there are also the specific pharmacokinetics and the fast body mass and composition change of newborns, making them particularly susceptible to the risks of developing adverse drug reactions (ADRs) or experiencing errors in adjusting doses or formulations. 5,6,9,10 In 2010, European Medicines Agency (EMA) published a report that describes existing data on paediatric uses of medicinal products by country.…”
Section: Introductionmentioning
confidence: 99%
“…2. It is reported that the number of medications administered in the NICU is inversely proportional to the patients gestational age or their weight [Carvalho et al 2012]. …”
mentioning
confidence: 99%
“…Nesta edição do Jornal de Pediatria, Carvalho et al 9 Não foram declarados conflitos de interesse associados à publicação deste editorial.…”
unclassified
“…Nesta edição do Jornal de Pediatria, Carvalho et al 9 relatam os resultados de um estudo prospectivo observacional de coorte realizado no Brasil, que avaliou o uso de medicamentos off-label e não licenciados na UTIN. Seus resultados confirmam o que estudos prévios de outros países também haviam demonstrado: pouquíssimos pacientes (21%) medicados na UTIN atenderam aos requisitos para uso adequado.…”
unclassified